Charakterystyka polskiego stylu negocjowania - Bartnicka Beata (My University, 2003)
Otwieranie się rynków oraz powszechna globalizacja powodują coraz częstsze kontakty przedstawicieli różnych kultur. Właściwy i oczekiwany przebieg takich spotkań zależy tak od znajomości kultury partnera, jak i własnej. Styl negocjacyjny staje się jednym z kluczowych pytań w świetle negocjacji międzynarodowych. Każdy kraj ma swoisty zbiór zasad i norm, których znajomość istotnie ułatwia kontakty na rynku światowym. Studiując literaturę przedmiotu odnajdujemy wiele cennych wskazówek dotyczących negocjacji z większością przedstawicieli krajów świata. Tym samym powstaje potrzeba określenia charakteru negocjowania Polaków, tak w celu wskazania partnerom polskich negocjatorów pewnych zasad, preferencji i wartości Polaków, jak i dla samych Polaków, ułatwiając im tym samym proces doskonalenia i osiągania optymalnych wyników negocjacji. Próba odnalezienia polskiego stylu negocjowania nabiera szczególnego znaczenia dla dalszego rozwoju Polski głównie z perspektywy przyjęcia naszego kraju do Unii Europejskiej oraz wszelkich działań i konsekwencji postępującej globalizacji Podstawowym motywem niniejszej pracy staje się więc pytanie o istnienie polskiego stylu negocjacyjnego w świetle unifikacji rynków, a w dalszej części próba odnalezienia i charakterystyka polskiego stylu negocjacyjnego. W niniejszej pracy problem badawczy określono jako następujące pytania:Czy istnieje styl negocjowania właściwy dla Polaków? Czy na skutek powszechnej globalizacji i otwierania granic nie zanikają wartości kulturowe poszczególnych krajów? Jak negocjować z Polakiem? Postawiono hipotezę: istnieje polski styl negocjacyjny. Na skutek globalizacji i ujednolicania rynków światowych posiada on pewne cechy specyficzne dla innych kręgów kulturowych, w szczególności europejskich. W dużej jednak mierze polski styl negocjacyjny wciąż posiada swoją odrębność i specyfikę wynikające z historii Polski – wojen, zaborów, ustroju socjalistycznego oraz ruchu społecznego Solidarność.

Cultural interpretation and adaptation are prerequisites to the understanding of national and international business practice, especially when the purpose of a negotiation is to achieve a win-win relationship, rather than a win-lose relationship. The greater the cultural differences, the more likely barriers to communicate. Studies of cultural negotiating styles tend to divide into two basic groups. The first describe and analyze the negotiating style of a particular culture. This attitude seeks to lead the novice through the intricacies of negotiating in specific countries. The second approach is cross cultural and comparative. It seeks to identify certain basic elements in negotiating style and to determine how they are reflected in various cultures. The great diversity of the world's cultures makes it impossible for any negotiator, no matter how skilled and experienced, to understand fully all the cultures that he or she may encounter. That negotiation style so effectively used domestically can be inappropriate when dealing with people from another cultural background. When negotiating internationally, this translates into anticipating culturally related ideas that are most likely to be understood by a person of a given culture. Heightened sensitivity, more attention to detail, and perhaps even changes in basic behavioral patterns are required when working in another culture. Different cultural systems can produce divergent negotiating styles shaped by each nation's culture, geography, history, and political system. The goal of this paper was to find out the polish style of negotiation, whether it exists according to the unification of international trades and cultures, and progressing proces of globalization. When negotiating with Polish people, be patient in business dealings as decisions can take some time to be reached. Polish negotiators are always thoroughly prepared. It is warmly appreciated to express a knowledge of Polish history and culture as your Polish counterparts may well have an educated interest in the visitor's culture and current affairs. Titles carry prestige in Poland. Historically, a title signified a person's nobility or status as a landowner. Today it refers to educational attainment, profession, or administrative position. Once you know a person's title you should use it, especially in work situations, formal occasions and in any written communication. Conversational subjects to avoid include religion, politics, social and economic conditions in Poland. Allow you Polish counterpart to broach these subjects. Most Polish officials have a good sense of humor and a lot of good will for foreigners.
Keywords: negocjacje; konflikt; komunikacja; różnice kulturowe w procesie negocjacji; negocjatorzy; negocjacje-transakcje; biznes